„Pamięć, która jest trwalsza od prochów…” – rzecz o Annie Wazównie i mowie Martina Opitza jej poświęconej - Monika Wicha (Meluzyna: dawna literatura i kultura, 2018)
The article deals with the funeral of Anna Vasa, the sister of the Polish ruler Sigismund III Vasa. Young Anna Vasa decided to change her religion which influenced her further life. In consequence, her remains could not receive a solemn funeral for the next 11 years following her death. This text aims at analysing the work by German author Martin Opitz, which was ordered in commemoration by the Swedish princess’ nephew, Wladyslaw IV. Martin Opitz’s work, which undoubtedly brought him fame, is being analysed based on the rhetoric devices used by the author as well as the parenetic model of a woman that he created, based on the examples of the virtues of the deceased princess.